Geochemical and isotopic compositions of East Rift lavas from the Manus Basin: Implications for the origin of subduction components. (29th May 2020) - Wang, Xiong; Huang, Peng; Huang, Haijun; Hu, Ningjing
Abstract : Many recent studies have concluded that subduction components exist in the mantle source of the Manus back‐arc basin lavas; however, the origin of these components remains an ongoing controversy. The East Rift at the eastern end of the Manus Basin is ideal for investigating the subduction components because of its unique geographic location. In this study, 10 samples from the East Rift were selected for geochemical and isotopic analysis. The results show that these samples can be compositionally divided into basaltic andesite and dacite belonging to the medium‐K calc‐alkaline series. Furthermore, the parental magma experienced fractional crystallization. The analyses also indicate that the subduction components came from the Solomon Plate and consist of altered oceanic crust (AOC) and sediments. The AOC materials entered the mantle source through fluids, while the sedimentary materials were transferred as melts. Assuming 5% partial melting of the sediments and 1% fluid production from the AOC in a modal melting process of an eclogitic source, the results of endmember modelling of Pb isotopic data reveal that the subduction components beneath the East Rift area consist of approximately 60–65% AOC fluids and 35–40% sediment melts and that the source contains approximately 1–5% subduction components.